Analisis Manajemen Risiko Teknologi Informasi pada Dinkominfo Surabaya Menggunakan Metode Failure Mode and Effect Analysis (FMEA) - Fidyah Salsabila Putri Sillehu; Marisca Amanda Hidayat; Raihana Sakhi Aswanda; Audrey Septya Rosanti; Agung Brastama Putra; Amalia Anjani Arifiyanti (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The use of information technology (IT) in the government sector requires structured risk management to ensure the continuity of public services. The Department of Communication and Information Technology (Dinkominfo), as a digital service provider, faces various potential risks such as network disruptions, hardware failures, and cyberattacks that could interfere with daily operations. This study employs the Failure Mode and Effect Analysis (FMEA) method to identify, analyze, and formulate strategies to mitigate existing IT risks. Through the FMEA approach, each potential failure is evaluated based on its severity, occurrence, and detection capability, which are then used to calculate a Risk Priority Number (RPN). The analysis reveals that the highest RPN values are associated with information system errors, hardware failures, and network overloads. As mitigation measures, the study recommends conducting regular system audits, upgrading network capacity, and performing preventive maintenance on devices. This approach demonstrates that FMEA is an effective method for managing IT risks within government institutions.